The notion of lexical minimum and how to enhance lexical competence on B2 level - Muxtorov Muhiddin Mansur o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Nowadays the knowledge of English and being fluent in it is deemed as a major factor of success not only in everyday life but also in the sphere of education, since it opens new vistas for students and helps with their future career. However, since there is insufficient for Uzbek students with foreigners and exposure to the English language, this situation presents difficulty for the learners to master the language on a high level. Consequently, learners tend to use their mother tongue due to their inadequate vocabulary. We think that much more attention should be paid on teaching vocabulary and developing of their lexical competence.